2023
DOI: 10.24996/ijs.2023.64.4.43
|View full text |Cite
|
Sign up to set email alerts
|

User Oriented Calibration Method for Stonex X300 Terrestrial Laser Scanner

Abstract: Terrestrial laser scanners (TLSs) are 3D imaging systems that provide the most powerful 3D representation and practical solutions for various applications. Hence this is due to effective range measurements, 3D point cloud reliability, and rapid acquisition performance. Stonex X300 TOF scanner delivered better certainty in far-range than in close-range measurements due to the high noise level inherent within the data delivered from Time of Flight (TOF) scanning sensors. However, if these errors are manipulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…It is worth mentioning that the geo-referencing process was applied based on the error-free assumption of the reference target measurements that were obtained from the ES-105 total station device. Furthermore, the empirical approach that was implemented in this research was based on calibrating the Stonex X300 device following the user-oriented routine that was explained in [21].…”
Section: Range-based Uncertainty Measurementioning
confidence: 99%
See 1 more Smart Citation
“…It is worth mentioning that the geo-referencing process was applied based on the error-free assumption of the reference target measurements that were obtained from the ES-105 total station device. Furthermore, the empirical approach that was implemented in this research was based on calibrating the Stonex X300 device following the user-oriented routine that was explained in [21].…”
Section: Range-based Uncertainty Measurementioning
confidence: 99%
“…Similar to most TOF scanners, The Stonex X300 was found to be more relevant for mid-range measurements than it was in close-range measurements due to its measuring principals (which are based on the pulse-ranging technique -as with most similar scanner devices) [4,20]. Even though this laser device is featured in limited range-analysis studies [21], the available studies have revealed the sufficiency of this device for close-range measurements if the measurements have analyzed and signal-to-noise error impacts that are correctly eliminated. For example, [22] presented a practical study to use the Stonex X300 for structural health monitoring (SHM) in a close-range environment.…”
Section: Introductionmentioning
confidence: 97%